Os TEIP pela perspectiva de pais e alunos - Quaresma, Luísa (2011)
Based on the results of a recent study on the Educational Territories of Priority Intervention carried out in four groupings of schools (two in Lisbon Metropolitan area and another two in Porto), we will discuss cross-representations of parents and students about this school reality, evidencing satisfaction factors and dimensions of rejection, often crystallised around stereotypes resulting from a number of projects and modes of relationship with the school. There is strong visibility of convivial and fun appropriations of school spacetimes by pupils, as well of the growing importance of affective dimension of learning and teaching, increasingly supported by professionals of mediation. At the same time, one noticed notorious social and symbolic divisions trough parents attitudes and opinions.